ON RECENT FAULTS AND PALEOSEISMIC FRACTURES IN THE PALAEOPROTEROZOIC ONEGA STRUCTURE OF THE BALTIC SHIELD - Андрей Алексеевич Никонов; Антон Владимирович Полещук; Дмитрий Сергеевич Зыков; Andrey Nikonov; Anton Poleshchuk; Dmitry Zykov (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2017)
Specific morphological structures corresponding to impulsive seismotectonic events were identified within the Onega structure of the Fennoscandian (Baltic) shield of the East European platform. Analysis of data from the literature showed that similar morphological structures have been detected by Russian scientists in this area already since the 19th century. The study of evolution, kinematics, and the correlation of the morphostructures with the region’s Palaeoproterozoic geological structure suggest that recent tectonic movements have been accommodated to the ancient structure. In particular, late- and postglacial faults were found to be associated to this structure. We prove that a majority of the identified morphostructures are dislocations caused by strong seismic impacts in a number of areas. The prolonged evolution of the Palaeoproterozoic intracontinental morphostructures is confirmed, and the possibilities for refining the estimates of longterm seismic hazard in the area of tectonic accommodation of the Fennoscandian shield in the central sector of the Polkanov flexure are expanded.